Tailored Microstructured Hyperpolarizing Matrices for Optimal Magnetic Resonance Imaging. Issue 25 (15th March 2018) - Cavaillès, Matthieu; Bornet, Aurélien; Jaurand, Xavier; Vuichoud, Basile; Baudouin, David; Baudin, Mathieu; Veyre, Laurent; Bodenhausen, Geoffrey; Dumez, Jean‐Nicolas; Jannin, Sami; Copéret, Christophe; Thieuleux, Chloé
Abstract: Tailoring the physical features and the porous network architecture of silica‐based hyperpolarizing solids containing TEMPO radicals, known as HYPSO (hybrid polarizing solids), enabled unprecedented performance of dissolution dynamic nuclear polarization ( d ‐DNP). High polarization values up to P ( 1 H)=99 % were reached for samples impregnated with a mixture of H2 O/D2 O and loaded in a 6.7 T polarizer at temperatures around 1.2 K. These HYPSO materials combine the best performance of homogeneous DNP formulations with the advantages of solid polarizing matrices, which provide hyperpolarized solutions free of any—potentially toxic—additives (radicals and glass‐forming agents). The hyperpolarized solutions can be expelled from the porous solids, filtered, and rapidly transferred either to a nuclear magnetic resonance (NMR) spectrometer or to a magnetic resonance imaging (MRI) system. Abstract : A matter of polarization : Porous silica‐based solids functionalized with TEMPO surface groups were designed and used to achieve remarkable proton and carbon polarization values by dynamic nuclear polarization. These materials were successfully used as polarizing matrices for 13 C magnetic resonance imaging.